MEDIASI ANTARA KONSUMEN DAN PELAKU USAHA PADA TRANSAKSI E-COMMERCE - VERRA SELY AUDIAWATY; Firdaus Firdaus; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
E-commerce connects business actors, consumers and other communitiesthrough electronic transactions to trade in goods, services and other information.This condition causes distance is no longer a barrier in the business world.Barriers such as the process of solving the problem of buying and sellingtransactions. This study seeks to analyze the completion of the mediation processbetween business actors and consumers which is completed by involving the e-commerce service providerThis type of research can be classified as normative legal research,namely legal research conducted by researching library materials. This studyexamines the subject matter in accordance with the scope and identification of theproblem through the statute approach, which is carried out by examining the lawsand regulations related to the legal issues under study. In this study the authorsconducted research on legal principles by utilizing descriptive methods. The datacollection technique used in Normative Legal Research is a library researchmethod, namely utilizing the library as a means of collecting data, by studyingbooks as reference materials related to the problems to be studied.The conclusions that can be drawn from the results of the study are: First,the completion of the mediation process between business actors and consumersis carried out in the context of a quick and simple settlement and relatively lowcourt costs with the results of the settlement being acceptable to both parties tothe dispute without causing new problems or prolonging the dispute. Thecompletion of the mediation process between business actors and consumers wasnot carried out properly. Business actors show an uncooperative attitude inresolving efforts. This is because in the process of resolving the mediation,business actors do not show good faith in responding to complaints fromconsumers. Business actors show an uncooperative attitude in resolving efforts.Second, the mediation process between business actors and consumers was notcarried out as well as each of the above stages. This is because in the mediationprocess the consumer does not refer to and does not know the stages mentionedabove.Keywords: Mediation, Consumers, Business Actor, E-Commerce Transactions